2022
DOI: 10.3390/nu14081605
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Calorie Paradigm: Taking into Account in Practice the Balance of Fat and Carbohydrate Oxidation during Exercise?

Abstract: Recent literature shows that exercise is not simply a way to generate a calorie deficit as an add-on to restrictive diets but exerts powerful additional biological effects via its impact on mitochondrial function, the release of chemical messengers induced by muscular activity, and its ability to reverse epigenetic alterations. This review aims to summarize the current literature dealing with the hypothesis that some of these effects of exercise unexplained by an energy deficit are related to the balance of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 330 publications
0
12
0
Order By: Relevance
“…In this regard, it is interesting to note that our research indicated the importance of RXFP3 in glucometabolic activity [127][128][129][130], while GPR19 has been more strongly associated with lipid metabolism [131,132]. In this respect, perhaps simplistically, RXFP3 and GPR19 may function as "yin and yang" in the realm of the balance between glucose or lipid metabolic functionality [18,23,[133][134][135][136]. Thus, it may be likely that GPCR systems could possess a nuanced level of interaction between the multiple stress-related factors that control molecular aging [33].…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, it is interesting to note that our research indicated the importance of RXFP3 in glucometabolic activity [127][128][129][130], while GPR19 has been more strongly associated with lipid metabolism [131,132]. In this respect, perhaps simplistically, RXFP3 and GPR19 may function as "yin and yang" in the realm of the balance between glucose or lipid metabolic functionality [18,23,[133][134][135][136]. Thus, it may be likely that GPCR systems could possess a nuanced level of interaction between the multiple stress-related factors that control molecular aging [33].…”
Section: Discussionmentioning
confidence: 76%
“…However, the sugar consumption rate in Tabata is notably higher than in the other two groups. Exercise intensity influences the efficiency of sugar oxidation during exercise, and as the intensity increases, so does the efficiency of sugar oxidation metabolism ( 23 ). High-intensity exercise results in rapid glycogen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This rise in adipose tissue TG lipolysis, and potentially IMTG utilization, is mediated by an augmented response of catecholamines to exercise (Liu et al, 2020). During physical exercise, both lipids and carbohydrates are oxidized at the same time, although their proportional contributions as fuel sources are controlled by a variety of circumstances (Brun et al, 2022;Pi et al, 2023). These variables include the type of exercise undertaken, the length of the exercise session, and the level of physical activity (Gordon et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%